ANALYSIS OF THE JUDGE'S VERDICT ON THE CRIMINAL ACT OF MONEY DOUBLING FRAUD COMMITTED BY THE PARANORMAL - Levi Olivia (Law Faculty of Universitas Bandar Lampung, 2021)
Association is often abused, or also utilizes relationships that have been established so well. Many cases of fraud between friends of a certain group where the relationship is already well established, on the grounds of their economy by daring to commit a criminal act of fraud to their own friends. The problem in this study is 1) what is the factor that causes the criminal act of money doubling fraud committed by psychics?, 2) how is the law enforcement process against the perpetrators of money doubling fraud?, 3) how is the consideration of hakin against the perpetrators of money doubling fraud? The methods used in this research are through normative juridical approaches, and empirical approaches using secondary data and primary data, data abalysis using qualitative analysis. Based on the results of the research, it can be concluded that the factors that cause the criminal act of money doubling fraud committed by the paranormal is due to economic, educational, social and environmental factors, the law enforcement process against the perpetrators of fraud crimes is carried out by the police, prosecutors and decided in court while the judge's consideration of the perpetrators of fraud fraud is multiplied by the paranormal based on article 378 of the Kuh. P Jo Article 55 Paragraph (1) and sentenced to imprisonment for 1 (one) year 6 (six) months. The advice in this study is to be more wary of all sorts of forms of deception, albeit with various seductions, because being confident and believing sudan's sustenance is governed by Allah SWT not in the way that psychics do. Law enforcement officials in sanctioning the accused must pay attention to the non juridical aspect of the perpetrator's actions.